Searching for a common host: parasitoids of Lema daturaphila on Datura stramonium in Central Mexico - Carol Estefanía Villanueva-Hernández; Juan Núñez-Farfán (PeerJ, 2025)
Background Natural enemies of herbivore insects can change the arms race between plants and insects. Their presence and abundance even can affect the co-evolution of interacting species. The annual herb Datura stramonium varies geographically in the extent of its direct defenses against herbivores. Its main specialist herbivore, Lema daturaphila, is adapted to cope with these defenses, but little is known about its natural enemies. Here, we determined the presence and incidence of L. daturaphila parasitoids as an initial step to explore other ecological and evolutionary relationships in a tri-trophic context. Methods Field collections of L. daturaphila eggs and larvae were performed during the summers of 2018 and 2019 in eleven natural populations of D. stramonium in central Mexico. We recorded their development to evaluate the emergence of parasitoids and their relationship with the abundance of herbivore individuals and environmental variables in each locality. Results We found six parasitoid fly and wasp species that are new records for Mexico or the host. Throughout their distribution, the interaction varies widely among populations and years. In some localities, egg parasitoids dominate over larval parasitoids and vice versa, and they exert strong pressures on the survival of L. daturaphila’s populations. The abundance of Emersonella lemae, the egg parasitoid, is related to the clutch size of L. daturaphila and climatic conditions such as temperature, altitude, and precipitation. As an apparent defense strategy against parasitoid flies, larvae of L. daturaphila release their oral secretions, which contain alkaloids from D. stramonium. At a geographic scale, these findings change the scenario between the plant-herbivore interaction and open the field to explore the different selective pressures among populations.